2021
DOI: 10.3390/biom11020229
|View full text |Cite
|
Sign up to set email alerts
|

TRPM4 in Cancer—A New Potential Drug Target

Abstract: Transient receptor potential melastatin 4 (TRPM4) is widely expressed in various organs and associated with cardiovascular and immune diseases. Lately, the interest in studies on TRPM4 in cancer has increased. Thus far, TRPM4 has been investigated in diffuse large B-cell lymphoma, prostate, colorectal, liver, breast, urinary bladder, cervical, and endometrial cancer. In several types of cancer TRPM4 is overexpressed and contributes to cancer hallmark functions such as increased proliferation and migration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 133 publications
(217 reference statements)
2
24
0
Order By: Relevance
“…associated with cancer stemness before, one of them being the TRPM4 gene, a member of the TRPM family of ion channels [15]. TRPM4 is known to be overexpressed in breast [16] and other types of cancer [47]. We confirmed these data by interrogating the Oncomine data base [48].…”
Section: Trpm4 Is Overexpressed In Mcf-7 Mammospheressupporting
confidence: 67%
See 2 more Smart Citations
“…associated with cancer stemness before, one of them being the TRPM4 gene, a member of the TRPM family of ion channels [15]. TRPM4 is known to be overexpressed in breast [16] and other types of cancer [47]. We confirmed these data by interrogating the Oncomine data base [48].…”
Section: Trpm4 Is Overexpressed In Mcf-7 Mammospheressupporting
confidence: 67%
“…The TRPM4 channel is only permeable to monovalent cations, mostly to Na + and K + , upon activation by an increase in intracellular Ca 2 + [15]. Most interestingly to us, TRPM4 protein levels are increased in a variety of tumor types compared to healthy tissue, where it contributes to important cancer features, such as increased proliferation and migration and cell cycle shift (reviewed in [15,47]). Particularly in breast cancer, two recent studies showed that both the mRNA and protein levels of TRPM4 were upregulated in specimens from breast cancer patients [16,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPM4 is broadly expressed in several tissues (141) and modulates several cell functions, including insulin secretion (143), immune response (144), cell migration and contractility (145,146). TRPM4 also plays an important role in disease and several evidences has emerged linking the expression of TRPM4 with the increase of migration, invasion and proliferation of certain cancers, such as lymphoma (147), cervical (148), colorectal channel, prostate cancer (149)(150)(151) and others (152). Moreover, upregulation of this channel is associated with poor prognosis in large B cell lymphoma, breast cancer and endometrial carcinoma, while its overexpression increases the recurrence risk in prostate cancer (153)(154)(155)(156).…”
Section: Trpm4mentioning
confidence: 99%
“…However, some preliminary findings suggest that dysregulation of some members may be involved in lymphoma. In this regard, TRPM4 overexpression has been found in B-cell large lymphoma (DLBCL) [109].…”
Section: Trp Channels In Hlsmentioning
confidence: 99%